An Acromegalic Patient with Sickle Cell Disease Undergoing Endoscopic Trans-Sphenoidal Surgery: Anesthetic Concerns for a Neuroanesthesiologist - Thappa, Priya; Panda, Nidhi B. (Journal of Neuroanaesthesiology and Critical Care, 2023)
Sickle cell disease (SCD) refers to a group of hemoglobinopathies that include mutations in the gene encoding the β subunit of hemoglobin. The glutamine in the heme portion of the hemoglobin molecule is abnormally substituted by valine. Sickle hemoglobin (hemoglobin type S), when gets deoxygenated, tends to polymerize and aggregate leading to vaso-occlusion and organ ischemia. Such patients are at increased risk of perioperative mortality and severe complications like vaso-occlusive crisis, acute chest syndrome, and congestive heart failure. We describe the perioperative management of a case of SCD with acromegaly scheduled for trans-sphenoidal removal of a functional pituitary adenoma. The acromegalic habitus, the cardiovascular effects of acromegaly, and the hormonal imbalances due to pituitary adenoma pose challenges in addition to the challenge of preventing complications of SCD making the anesthetic management more exigent.
Keywords: acromegaly; anesthesia; sickle cell disease